Patient outcomes in a PD First Program in Cape Town, South Africa - Davidson, Bianca (Division of Nephrology and Hypertension, 2018)
Background: South Africa [SA] currently performs the most peritoneal dialysis [PD] in Africa. Yet, outcome data is limited. With the collision of epidemics of communicable and non-communicable diseases in Africa the need for chronic dialysis is escalating. PD remains a life-saving modality especially as haemodialysis is limited in the state sector. Methods: We retrospectively analysed all patients undergoing PD at Groote Schuur Hospital from January 2008 until June 2014 and thereafter prospectively until June 2015. Variables included demographics, adequacy, modality, fluid, cardiovascular risk and diabetes. The influences of these variables on peritonitis rate, technique and patient survival were assessed. Results: 230 patients were initiated on PD, 31 were excluded as they were on PD for < 90 days. The mean age was 39.7 +/- 10.4 years [SD], 49.8% were male and 63.8% were mixed ancestry. 9.8 % were diabetic at dialysis initiation. The average length of time on PD was 17 months (IQR 8 - 32). The peritonitis rate was 0.87 events per patient years. One, 2 and 5 year patient and technique survival was 94.4%, 84.3% and 60.2% and 82.5%, 69.0% and 37.4% respectively. Fluid overload (p=0.019) and low haemoglobin (p=0.001) were independent risk factors for poor survival. African race (HR 1.97, 95% CI (1.16 - 3.37) and fluid overload (p= 0.002) were both predictors of technique failure. Conclusions: In our PD-First programme the results are encouraging, despite lack of home visits due to safety, resource limitations and a high disease burden. Technique failure in African race needs further evaluation. Peritoneal dialysis remains a viable, life-saving alternative in an African setting.